Eucalyptus urograndis physiological and hormonal changes under drought conditions in response to trinexapac-ethyl - Bacha, Allan Lopes [UNESP]; Santos, Renata Thaysa da Silva; Braga, Andreísa Flores [UNESP]; Rodrigues, Juliana de Souza; Carrega, Willians César [UNESP]; Bergua, Esther Carrera; Grey, Timothy Lane; Alves, Pedro Luís da Costa Aguiar [UNESP] (Elsevier, 2024)
Previous studies have reported that trinexapac-ethyl (TE) stimulates growth of well-watered (WW) eucalypt plants. However, the physiological and hormonal changes in response to this chemical remain unclear. Furthermore, there are reports that this chemical attenuates drought responses in grasses. This research investigated the hormonal and physiological response of Eucalyptus urograndis (Clone 1407) plants treated with TE, cultivated under WW and drought conditions. The experiment was carried out in a greenhouse up to 42 days after application of 0, 90 and 150 g ha−1 of TE. Eucalypt growth, hormone concentration, gas exchange, maximum quantum yield of photosystem II and total relative chlorophyll content were evaluated. TE increased growth of WW plants by up to 65%. Drought restricted the stimulatory effects of TE on eucalypt growth, despite an increase of at least 102% in gibberellin A4 (GA4), trans-zeatin (tZ) and N6-isopentenyladenine (iP) concentrations after application. GA4 stood out as an indicator of drought stress as it increased almost 6-fold compared to WW eucalypt. TE caused a hormonal imbalance in eucalypt up to 42 days after application, increasing GA1 concentration as a short-term effect (8 days) and GA8 as a medium-term effect (42 days). Gibberellin homeostasis was not reestablished until 42 days after TE treatment. These results provide insights into eucalypt hormonal response to TE. Future research should be conducted under field conditions to understand how long such positive effects would be detected over time in short-rotation eucalypt plantations.
Keywords: Abiotic stress; Gas exchange; Gibberellins; Hormone crosstalk; Plant growth regulator; Stimulatory effect